Nitrite and Nitrate Levels of Gingival Crevicular Fluid and Saliva in Subjects with Gingivitis and Chronic Periodontitis - Ali Orkun Topcu; Ferda Alev Akalin; Kemal Burak Sahbazoglu; Nermin Yamalik; Kamer Kilinc; Erdem Karabulut; Tolga Fikret Tözüm (Stilus Optimus, 2014)
Objectives: Nitrosative stress plays an essential role in the pathogenesis of periodontal disease. The aim of this study is to analyze the gingival crevicular fluid and saliva nitrite and nitrate levels in periodontally healthy and diseased sites. Material and Methods: A total of 60 individuals including, 20 chronic periodontitis and 20 gingivitis patients and 20 periodontally healthy controls participated in the present study. Probing depth, clinical attachment level, bleeding on probing, gingival index and plaque index were assessed, gingival crevicular fluid (GCF) and saliva samples were obtained from the subjects, including 480 GCF samples and 60 unstimulated whole saliva samples. Nitrite and nitrate were analyzed by Griess reagent. Results: Total GCF nitrite levels were higher in gingivitis and periodontitis groups (1.07 [SD 0.62] nmol and 1.08 [SD 0.59] nmol) than the control group (0.83 [SD 0.31] nmol) (P < 0.05) but did not differ significantly between gingivitis and periodontitis groups (P > 0.05). The difference in GCF nitrate level was not significant among the control, gingivitis and periodontitis groups (7.7 [SD 2.71] nmol, 7.51 [SD 4.16] nmol and 7.38 [SD 1.91] nmol). Saliva nitrite and nitrate levels did not differ significantly among three study groups. Saliva nitrate/nitrite ratios were higher in periodontitis and gingivitis groups than the control group. A gradual decrease in nitrate/nitrite ratio in GCF was detected with the presence of inflammation. Conclusions: It may be suggested that nitrite in gingival crevicular fluid is a better periodontal disease marker than nitrate and may be used as an early detection marker of periodontal inflammation, and that local nitrosative stress markers don't show significant difference between the initial and advanced stages of periodontal disease.